Formulation of Floating Microspheres of Ritonavir by Crosslinking-Technique: Effect of NaHCO3 as Gas Forming Agent - Harsoliya, M.S. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTFloating microspheres of Ritonavir was prepared by simple dripping method with an aim of increasing the gastric residence time and for controlled release. A polymeric mixture of Sodium alginate and hydroxy propyl methylcellulose was used. Sodium bicarbonate was used as the gas-forming gent. The solution was dropped to 1% calcium chloride solution containing 10 % acetic acid for carbon dioxide release and gel formation. The prepared floating microspheres were evaluated with respect to particle size distribution, floating behavior, drug content, entrapped, morphology and in vitro release study. Effect of sodium bicarbonate on the above mentioned parameters were evaluated and it was found that the sodium bicarbonate had a pronounced effect on various parameters. The enhanced buoyancy and controlled release properties of sodium bicarbonate containing microspheres made them an excellent candidate for floating dosage form.